Constructing site quality curves and productivity assessment for uneven-aged and mixed stands of oriental beech (Fagus oriental Lipsky) in Hyrcanian forest, Iran. Issue 1 (2nd January 2017) - Ahmadi, Kourosh; Alavi, Seyed Jalil; Kouchaksaraei, Masoud Tabari
ABSTRACT: In the domain of sustainable forest management, site productivity assessment is a major forestry topic. The reliable estimates of site quality are crucial for improved predictions of timber yields and for meaningful simulation studies. Site quality curves were constructed and assessed for beech forests in a Hyrcanian forest, located in the north of Iran. A measure of the site quality concept known as site form (i.e. the expected mean height at 75 cm diameter at breast height) was used. One hundred and twenty seven 0.1 ha circular sample plots were established covering soil and topographic variations in Tarbiat Modares University Experimental Forest. Site productivity curves were constructed using a difference equation approach in the context of the Chapman-Richards model and the Edminster el al. (1991) method. After estimating site form for each plot, they were divided into three categories (poor, medium, and good). Ordinal logistic regression model of site form on soil and topographic variables were fitted using the free statistical programming language 'R'. The results showed that only the percentage of clay, altitude, and phosphorous were significant at 0.05 significance level (Nagelkerke pseudo-R-squared = 51.58%). The results of this study suggest that site form appears to be a potentially useful indicator of site quality in mixed and uneven-aged forests.